2001
DOI: 10.1002/jmv.2005
|View full text |Cite
|
Sign up to set email alerts
|

Area under the viraemia curve versus absolute viral load: Utility for predicting symptomatic cytomegalovirus infections in kidney transplant patients

Abstract: A novel approach to predicting symptomatic cytomegalovirus (CMV) infections combines the level and the duration of viraemia in a single parameter. Sixty-four kidney transplant recipients were monitored by quantitative shell vial culture, pp65 antigenaemia, and polymerase chain reaction (PCR) of leucocytes. The area under the curve (AUC) of each parameter was determined from the onset of viraemia to the beginning of antiviral treatment. The AUC values were significantly higher in symptomatic than in asymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
0
31
1
Order By: Relevance
“…The severity of an episode of CMV viremia is determined not only by its level but also by its duration (25,26). Both quantities can be combined by calculation of the area under the curve of viral load over time (25), a universal means of assessing the interrelationship among peak viral load, initial viral load, and rate of increase of viral load, parameters that have been described as independent risk factors for CMV disease (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of an episode of CMV viremia is determined not only by its level but also by its duration (25,26). Both quantities can be combined by calculation of the area under the curve of viral load over time (25), a universal means of assessing the interrelationship among peak viral load, initial viral load, and rate of increase of viral load, parameters that have been described as independent risk factors for CMV disease (26).…”
mentioning
confidence: 99%
“…Both quantities can be combined by calculation of the area under the curve of viral load over time (25), a universal means of assessing the interrelationship among peak viral load, initial viral load, and rate of increase of viral load, parameters that have been described as independent risk factors for CMV disease (26). In this retrospective study, (re)activation of CMV, as measured by DNA load in plasma, was used as a safety parameter to evaluate the efficacy of ATG versus daclizumab in SPK transplant recipients.…”
mentioning
confidence: 99%
“…Moreover, determination of the CMV viral loads in blood (6,13,(16)(17)(18) and urine (8) has shown its utility in designating patients who at risk for * Corresponding author. Mailing address: Clinical Microbiology/ L40, The Cleveland Clinic Foundation,…”
mentioning
confidence: 99%
“…Moreover, determination of the CMV viral loads in blood (6,13,(16)(17)(18) and urine (8) has shown its utility in designating patients who at risk for disease (12). The clinical utility of the CMV viral load in BAL fluid has not been determined, however (1,15 Therefore, in the present study, we investigated the utility of the CMV Hybrid Capture assay (Digene Corporation, Gaithersburg, Md.)…”
mentioning
confidence: 99%
“…These studies have shown that viral load is a dominant risk factor for HCMV disease (Cope et al 1997;Gor et al 1998;Spector et al 1998;Emery et al 1999a,b;Hassan-Walker et al 1999;Limaye et al 2001). In addition, kinetics of replication during the early phases of active replication have been defined and used to estimate the basic reproductive number of HCMV (Emery et al 2002) and to provide prognostic information in the immunocompromised host (Emery et al 2000;Schafer et al 2001). Since the virologic parameters, such as initial viral load, peak viral load, rate of increase in viral load prior to disease onset, are highly correlated it has been difficult, using conventional multivariable models, to ascertain the relative contributions of viral load thresholds and continuous presence of virus to the pathogenesis of different HCMV diseases and to produce estimates of the likely time of onset of disease.…”
Section: Introductionmentioning
confidence: 99%